Simon Ellis, spelling bee champ - Mills, Claudia; Shepperson, Rob (2015)
Simon Ellis and the rest of the third grade Franklin School Friends participate in a spelling bee where Simon's competitive spirit takes over until he realizes that sometimes the best way to win is to take a chance and let other people shine.
Keywords: Spelling bees -- Fiction; Competition (Psychology) -- Fiction; Winning and losing -- Fiction; JUVENILE FICTION / School & Education; JUVENILE FICTION / Social Issues / Friendship